Turn-based strategy video game to inspire youths to adopt sustainable lifestyle habits - Lim, Jia Jing (Nanyang Technological University, 2023)
Climate change is a pressing issue that threatens humanity, and novel solutions are needed to combat it. Computer games have the potential to engage and motivate various stakeholders, including the public, to act on climate change. However, there is a lack of games that empower individuals to make a meaningful impact. This project aims to address this gap by developing a game that shows the impact of individual actions on climate change. The game is targeted towards Singapore youth and considers the unique characteristics of this demographic in the context of climate action. The game's design elements, including gameplay and mechanics, are carefully crafted to motivate and empower players to take action. This project is done in collaboration with Earthlink NTU, the largest environmental and sustainability outreach club in Nanyang Technological University. Earthlink NTU's expertise in environmental outreach and education is leveraged to ensure that the game is effective in engaging and educating Singapore youth on climate action.